2022
DOI: 10.3389/fenvs.2022.947014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rape/common vetch intercropping on biomass, soil characteristics, and microbial community diversity

Abstract: Legume–brassica intercropping is widely used to increase productivity in modern, sustainable agricultural systems. However, few studies have assessed the linkages between soil properties and soil microorganisms. Soil microorganisms play a key role in soil nutrient turnover and plant community composition. To elucidate the responses of soil microbial community diversity and structure to intercropping, we conducted a 2-year experiment based on common vetch (CV) monoculture, rape (R) monoculture, and common vetch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
(30 reference statements)
2
3
0
Order By: Relevance
“…Intercropping with legumes notably increased the concentrations of microbial C and N in the soil. This finding aligns with that of Qu et al. (2022) , who revealed significant increases in MBC and MBN under intercropping, directly proving the notion that enhanced stimulation of the microbial community can be achieved through intercropping.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Intercropping with legumes notably increased the concentrations of microbial C and N in the soil. This finding aligns with that of Qu et al. (2022) , who revealed significant increases in MBC and MBN under intercropping, directly proving the notion that enhanced stimulation of the microbial community can be achieved through intercropping.…”
Section: Discussionsupporting
confidence: 88%
“…Intercropping with legumes notably increased the concentrations of microbial C and N in the soil. This finding aligns with that of Qu et al (2022), who revealed significant increases in MBC and MBN under intercropping, directly proving the notion that enhanced stimulation of the microbial community can be achieved through intercropping. This enhancement may stem from the strong correlation observed between total microbial biomass and soil C concentration (Goyal et al, 1993;Elfstrand et al, 2007).…”
Section: Response Of Soil Properties To Different Intercropping Treat...supporting
confidence: 88%
See 2 more Smart Citations
“…Crops cover could directly change the abundance of microorganisms in the rhizosphere soil. For example, crops cover significantly reduces microbial biomass (Qu et al, 2022) and changes the richness of N‐fixing bacteria in rhizosphere soil (Hao et al, 2021; Xie et al, 2022). Differences in soil nutrients and microbial communities may further lead to differences in microbial metabolism between rhizosphere and bulk soils (Cui et al, 2022).…”
Section: Introductionmentioning
confidence: 99%